Produção de biomassa e lipídeos por Rhizopus arrhizus var. arrhizus UCP 1295 utilizando substratos renováveis em fermentação submersa. - Novaes, Camila Freire (2020)
Investigations were carried out with Rhizopus arrhizus var. arrhizus UCP 1295 in the conversion to biomass and lipid production using agro-industrial residues. The initial studies with the disposal of carrot (Daucus carota L.), yeast extract and peptone, a solution rich in mineral salts, in submerged fermentation. Employing a complete factorial design 23, to evaluate the influence of the components of the medium in the yield of biomass and lipids. The results showed in condition 8 with the highest biomass yield (8.11 g / L) and accumulation of more than 35% of lipids. However, the maximum production of lipids was 64.44%, in condition 1 (2% of discarded carrots and 1% of peptone), indicating that carrots are a promising carbon source for lipid accumulation. Then, comparative studies were carried out with the cassava peel (Monihot esculenta), residue from the indigenous village from the production of flour and with crude glycerol, supplementing with conventional substrates yeast extract and peptone, using complete factorial design 23, to evaluate the influence of the components of the medium in the biomass yield and accumulation of lipids by Rhizopus arrhizus var. arrhizus UCP 1295. The results indicated that condition 8 (6% of cassava peels, 1% of yeast extract and 3% of peptone) influenced the increase in biomass production (12.92 g / L), being observed 398.02 mg of lipids per g of biomass, corresponding to 30.42%. However, in percentage, the highest accumulation of lipids was observed in condition 7 (2% of cassava peels, 1% of yeast extract and 3% of peptone), with 35.39% of lipids. The use of crude glycerol was observed higher biomass production in test 6 (5% crude glycerol and 3% peptone), producing 22.1 g / L of biomass, 699.60 mg of lipids per g of biomass, corresponding to 31.64% of lipids, making it the most efficient medium in the production of biomass and lipids, being the most economical medium due to the absence of yeast extract. These results were confirmed by the Pareto diagrams. Comparing the results obtained with carrot and cassava residue, it is observed that carrots provided high lipids, probably due to the higher carbon content, an essential source for lipid accumulation. The biomasses formed rich in lipids generate prospects for use in animal feed, in the area of food and cosmetics.